2020
DOI: 10.1002/smll.202000043
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Long‐Distance Photoactuation with Protein Additives

Abstract: Long-distance wireless actuation indicates precise remote control over materials, sensors, and devices that are widely utilized in biomedical, defence, disaster relief, deep ocean, and outer space applications to replace human work. Unlike radio frequency (RF) control, which has low tolerance toward electromagnetic interference (EMI), light control represents a promising method to overcome EMI. Nonetheless, long-distance lightcontrolled wireless actuation able to compete with RF control has not been achieved u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 75 publications
0
14
0
Order By: Relevance
“…Making full use of the simultaneous reduction of lysozyme and graphene oxide by TCEP, a multifunctional hybrid film with layered stacking structure was fabricated through an evaporation casting process (Figure 9c). [ 114 ] The amyloid‐like lysozyme aggregates adsorbed on the rGO nanosheets via hydrophobic interaction and π–π stacking, and promoted the stable dispersion of rGO in aqueous solution. The resultant rGO–amyloid hybrid film could form a homogeneous coating on a surface with robust biomimetic interfacial adhesion.…”
Section: Fabrication Of Amyloid‐based Organic–inorganic Hybrid Materialsmentioning
confidence: 99%
“…Making full use of the simultaneous reduction of lysozyme and graphene oxide by TCEP, a multifunctional hybrid film with layered stacking structure was fabricated through an evaporation casting process (Figure 9c). [ 114 ] The amyloid‐like lysozyme aggregates adsorbed on the rGO nanosheets via hydrophobic interaction and π–π stacking, and promoted the stable dispersion of rGO in aqueous solution. The resultant rGO–amyloid hybrid film could form a homogeneous coating on a surface with robust biomimetic interfacial adhesion.…”
Section: Fabrication Of Amyloid‐based Organic–inorganic Hybrid Materialsmentioning
confidence: 99%
“…To date, many actuators consisting of carbon nanomaterials and polymer layer still display slow responses (tens of seconds to a few minutes) and insufficient sensitivity in the actuation/recovery process triggered by solvent vapors and [ 7,13,14 ] light stimuli. [ 15–19 ] Zhang et al. [ 20 ] and Deng et al.…”
Section: Figurementioning
confidence: 99%
“…To date, many actuators consisting of carbon nanomaterials and polymer layer still display slow responses (tens of seconds to a few minutes) and insufficient sensitivity in the actuation/recovery process triggered by solvent vapors and [7,13,14] light stimuli. [15][16][17][18][19] Zhang et al [20] and Deng et al [21] reported respectively thermally and solvent responsive actuators with bilayer CNT/polyethylene composite, and graphene/epoxybased polymer. These actuators can be bent reversibly in water or acetone under the controlled of thermal and near-infrared light.…”
Section: Doi: 101002/mame202000502mentioning
confidence: 99%
“…The achieved nano-platform, GO/BaHoF5/PEG/NVP-AUY922, had excellent biocompatibility and made tumor cells more sensitive to hyperthermia, which could promote the development of low-laser-hazard PTT [ 28 ]. In the work of Zhao et al, photomodule single-layer reduced graphene oxide (rGO) has been organized into a well-defined multilayer stack with the help of amyloid-like protein aggregates [ 29 ]. The as-fabricated hybrid film reliably adheres to the plastic substrate with robust interfacial adhesion.…”
Section: Introductionmentioning
confidence: 99%